PELAKSANAAN PELAYANAN PUBLIK MELALUI SISTEM MOBILE ELKTRONIK (SIMOLEK) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PEKANBARU - Usman, Fadhly; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Implementation of public services through the Mobile Elektonik (SIMOLEK) system at the One Stop Service Integrated Service Office (DPMPTSP) Pekanbaru City is implemented to improve the quality of public services (licensing and non-licensing services) by providing the simplification of the system and improving access to services so it is expected to encourage community / business actors to manage licensing according to specification and requirement as legality in conducting business activities.In this research, the concept of the theory used refers to the theory of public service proposed by Dwiyanto (2006) suggests four criteria that can be used to assess the bureaucracy (organization) in providing excellent public services, namely public accountability, responsiveness, service orientation, and efficiency service. This research uses qualitative approach with descriptive method in describing the research result. Data collection techniques include interviews, observation and documentation studies.The results of the research show the implementation of public service through the Mobile Elektonik (SIMOLEK) system at the One Stop Service Integrated Service Office (DPMPTSP) Pekanbaru City, the giver and service system has been running well proven by the transparency of service, openness in the availability of information related to licensing services and non permissions needed by the community and accessible to facilitate the community in terms of business licensing online. However, the output (result) in pushing the target group (users of the service) has not been running optimally, the users of the services using SIMOLEK, dated January 5, 2018 there are 105 users who perform the installation of electronic mobile devices, while issuing licenses as legality of business activities (target group) reaching 3,500-4,000 every year. The low service users use SIMOLEK due to the low socialization directly to the target group (business actors) related to electronic mobile services (SIMOLEK) that impact the ignorance and doubt the community / service users to the service.Key Words: Public Service, Public Accountability, Responsiveness, Service Orientation, Service Efficiency.